Analisis Klausa dalam Teks Rekon pada Buku “Bahasa Indonesia Tingkat Lanjut Kelas XI SMA Kurikulum Merdeka” - Ahmad Idham Kholid; Diva Fajria Rahma; Cahyani Ismi Azizah; Sherly Anida Fahrina Putri; Asep Purwo Yudi Utomo; Dyah Prabaningrum (Pusat Riset dan Inovasi Nasional, 2023)
This research discusses the analysis of clauses in recon texts contained in Indonesian language school textbooks. This study was made to provide knowledge to the reader about the categories of clauses and their examples in sentences in the text. The data for this study are in the form of three recon texts, which contain the types of clauses found in the Advanced Indonesian Language Book for Class XI SMA Merdeka Curriculum. The technique employed in this study is a qualitative descriptive method where the data collected takes the form of words rather than numbers. The analysis technique used is syntactic and also uses note-taking techniques in data collection. Based on the research conducted, twenty-seven clauses were obtained according to the category of phrases or words that occupy the function of the predicate. The clause consists of 26 verb clauses, eight noun clauses, one numeral clause, and two prepositional clauses. A verb clause is a clause whose predicate elements are categorized as verbs. Noun clauses are clauses whose predicate elements are categorized as nouns. Numeralia clauses are clauses whose predicate elements are in the category of numerals. Based on these consequences, it can be formulated that the function of the results of this study is to facilitate the readers' understanding of clause analysis because it provides a detailed explanation accompanied by examples of phrases or words in each sentence that contains the type of clause.